2023
DOI: 10.1124/jpet.123.001819
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotectant Activity of Novel Water-Soluble Synthetic Neurosteroids on Organophosphate Intoxication and Status Epilepticus-Induced Long-Term Neurological Dysfunction, Neurodegeneration, and Neuroinflammation

Doodipala Samba Reddy,
Tanveer Singh,
Sreevidhya Ramakrishnan
et al.

Abstract: Organophosphates (OPs) and nerve agents are potent neurotoxic compounds that cause seizures, status epilepticus (SE), brain injury, or death. There are persistent long-term neurologic and neurodegenerative effects that manifest months to years after the initial exposure. Current antidotes are ineffective in preventing these long-term neurobehavioral and neuropathological changes. Additionally, there are few effective neuroprotectants for mitigating the long-term effects of acute OP intoxication. We have pionee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 107 publications
1
5
0
Order By: Relevance
“…In contrast to midazolam, neurosteroid treatment reduces DFP-induced SRS, epileptiform discharges, and HFOs, along with reduced interictal events, possibly explaining their disease-modifying features. These effects are consistent with neuroprotectant outcomes in neuropathological and behavior tests ( Reddy et al, 2024 ), indicating a robust protective activity of neurosteroid treatments. Further studies are needed to advance the potential of synthetic neurosteroids in mitigating the long-term neurologic effects following OP intoxication.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In contrast to midazolam, neurosteroid treatment reduces DFP-induced SRS, epileptiform discharges, and HFOs, along with reduced interictal events, possibly explaining their disease-modifying features. These effects are consistent with neuroprotectant outcomes in neuropathological and behavior tests ( Reddy et al, 2024 ), indicating a robust protective activity of neurosteroid treatments. Further studies are needed to advance the potential of synthetic neurosteroids in mitigating the long-term neurologic effects following OP intoxication.…”
Section: Discussionsupporting
confidence: 75%
“…Despite its superior protective effects, GX has certain limitations such as poor bioavailability, lack of aqueous solubility, short half-life, and rapid hepatic inactivation ( Reddy, 2023 ; 2024 ). We have developed novel analogs to overcome these limitations ( Reddy et al, 2024 ). Synthetic neurosteroids with greater water solubility and bioavailability offer a superior therapeutic profile for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…When tested in animal models of OPNA-induced RSE, these lead analogs effectively blocked RSE when given intramuscularly 40 minutes after DFP administration, indicating their efficacy in the DFP model. The lead analogs significantly reduced neuronal injury, neurodegeneration, and inflammation in the hippocampus and other regions ( Ramakrishnan et al, 2024 ; Reddy et al, 2024 ), suggesting their neuroprotectant potential to mitigate OPNA-induced brain damage. The most promising drug-like compounds are in advanced development as anticonvulsants and neuroprotectants for SE indications.…”
Section: Novel Synthetic Neurosteroids (Superganaxolones) For Rsementioning
confidence: 93%
“…Many analogs of brexanolone and ganaxolone structure have been designed and tested for anticonvulsant efficacy ( Reddy and Kulkarni, 2000 ; Hogenkamp et al, 2014 ; Qian et al, 2014 ; Blanco et al, 2018 ; Zorumski et al, 2019 ; Reddy, 2023 ). Several water-soluble analogs were synthesized (superganaxolones) with improved hydrophilicity, an essential feature for intravenous and injectable formulations ( Reddy, 2023 ; Reddy et al, 2024 ). These novel analogs are designed to exhibit subunit selectivity and preferential interaction with extrasynaptic GABA-ARs to achieve greater therapeutic outcomes than GX ( Fig.…”
Section: Novel Synthetic Neurosteroids (Superganaxolones) For Rsementioning
confidence: 99%
“…In an antiseizure study, Reddy’s team reported valaxanolone and lysaxanolone effectively protected against DFP-induced epileptic seizures and electrographic biomarkers of ictal activity ( Ramakrishnan et al, 2024 ). In a neuroprotection study, Reddy and the team found that valaxanolone and lysaxanolone significantly improved behavioral and memory deficits, correlated with their ability to reduce neurodegeneration and neuroinflammation ( Reddy et al, 2024 ). These findings provide insights into the potential of hydrophilic neurosteroid analogs to overcome the limitations of current neurosteroid products and provide new options for developing effective treatments for nerve agent-induced seizures and neurodegeneration.…”
Section: Nerve Agentsmentioning
confidence: 99%